The Estimation of Critical Angle in Climbing as a Measure of Maximal Metabolic Steady State - Baláš, Jiří; Gajdošík, Jan; Giles, David; Fryer, Simon (Frontiers in Physiology, 2022)
Purpose. Sport climbing is a technical, self-paced sport and the workload is highly variable and mainly localized to the forearm flexors. It has not proved effective to control intensity using measures typical of other sports, such as gas exchange thresholds, heart rate or blood lactate. Therefore, the purposes of the study were to 1) determine the possibility of applying the mathematical model of critical power to the estimation of a critical angle (CA) as a measure of maximal metabolic steady state in climbing, and 2) to compare this intensity with the muscle oxygenation breakpoint (MOB) determined during an exhaustive climbing task. Materials and Methods. Twenty-seven sport climbers undertook three to five exhaustive ascents on a motorized treadwall at differing angles to estimate CA, and one exhaustive climbing test with a progressive increase in angle to determine MOB, assessed using near infrared spectroscopy. Results. Model fit for estimated CA was very high (R2=0.99; SEE=1.1°). The mean peak-angle during incremental test was -17±5° and CA from exhaustive trials was found at -2.5±3.8°. Nine climbers performing the ascent 2° under CA were able to sustain the task for 20 min with perceived exertion at 12.1±1.9 (RPE). However, climbing 2° above CA led to task failure after 15.9±3.0 min with RPE=16.4±1.9. When MOB was plotted against estimated CA, good agreement was stated (ICC=0.80, SEM=1.5°). Conclusion. Climbers, coaches and researchers may use a predefined route with three to five different wall angles to estimate CA as an analogue of critical power to determine a maximal metabolic steady state in climbing. Moreover, a climbing test with progressive increases in wall angle using MOB also appears to provide a valid estimate of CA.